2021
DOI: 10.1017/s0950268820003106
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for death in tuberculosis patients requiring ICU care

Abstract: The prognostic factor for in-hospital mortality in tuberculosis (TB) patients requiring intensive care unit (ICU) care remains unclear. Therefore, a retrospective study was conducted aiming to estimate the in-hospital mortality rate and the risk factors for mortality in a high-burden setting. All patients with culture-confirmed TB that were admitted to the ICU of the hospital between March 2012 and April 2019 were identified retrospectively. Data, such as demographic characteristics, comorbidities, laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…Predictors of hospital mortality were age, high APACHE IV score, mechanical ventilation, vasopressor therapy, RRT and hypoalbuminemia. Hypoalbuminemia is likely reflective of the inflammatory state of acute TB infection or underlying poor nutritional status 5 11 33–38. Like published cohorts, requirement for mechanical ventilation, vasopressor and RRT was associated with lower survival 4 39 40.…”
Section: Discussionmentioning
confidence: 83%
“…Predictors of hospital mortality were age, high APACHE IV score, mechanical ventilation, vasopressor therapy, RRT and hypoalbuminemia. Hypoalbuminemia is likely reflective of the inflammatory state of acute TB infection or underlying poor nutritional status 5 11 33–38. Like published cohorts, requirement for mechanical ventilation, vasopressor and RRT was associated with lower survival 4 39 40.…”
Section: Discussionmentioning
confidence: 83%
“…However, previous studies have also shown no difference in mortality between patients who developed HAIs in the ICU and the group which did not have HAIs [Choudhuri et al, 2017]. Prolonged ICU stays, nosocomial infection with secondary sepsis, and multiple organ dysfunction syndromes were the leading causes of death for nosocomial infection patients in ICU [Dasgupta et al, 2015, Wang et al, 2016.…”
Section: Discussionmentioning
confidence: 88%
“…As a result, elevated WBC counts in TB patients may be related to the severity of lung involvement and provide an estimated risk of mortality [ 11 ]. During TB infection, the body produces leukocytes and macrophages as part of the immune mechanism to defend the body against invading Mycobacterium tuberculosis , which raises the total number of WBC [ 12 ]. The current study findings documented that every 10 3 cells/µL increment in WBC above the normal range increased the risk of death by 1.102.…”
Section: Discussionmentioning
confidence: 99%